Nanotechnology in Cancer Treatment - Fiering, Steve N.; Ivkov, Robert (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The collection is diverse in the topics covered as well as the contributors, who come from across the globe. The overall topic is inherently a complex one since it integrates the exceptional complexity of cancer biology and treatment with the large and rapidly growing number of potential nanostructures and modifications that could be applied to treatment. In both cancer and nanotechnology, a very small change of a relevant variable can generate exceptional variability in biological outcome, creating inherent challenges to clinical adoption. As with many high-potential fields in medicine, the recognition of exceptional potential for nanotechnology in cancer therapy, with associated expectations of rapid clinical impact, has been followed by disappointingly slow progress that highlights not failure but rather unrealistic expectations for rapid progress. We have passed that period of expected rapid clinical impact for nanoparticle treatment of cancer and are now well-entrenched in the more realistic phase of exploiting the easiest applications, in this case packaging of established chemotherapy drugs, while carefully studying the exceptional numbers of relevant variables that must be evaluated for efficacy and safety of innovative strategies. Although never as rapid as hoped, the progress is clear and clinical impact is growing.